Gate-tunable room-temperature ferromagnetism in two-dimensional Fe3GeTe2. (1st November 2018) - Deng, Yujun; Yu, Yijun; Song, Yichen; Zhang, Jingzhao; Wang, Nai; Sun, Zeyuan; Yi, Yangfan; Wu, Yi; Wu, Shiwei; Zhu, Junyi; Wang, Jing; Chen, Xian; et al.
Abstract Materials research has driven the development of modern nano-electronic devices. In particular, research in magnetic thin films has revolutionized the development of spintronic devices1, 2 because identifying new magnetic materials is key to better device performance and design. Van der Waals crystals retain their chemical stability and structural integrity down to the monolayer and, being atomically thin, are readily tuned by various kinds of gate modulation3, 4 . Recent experiments have demonstrated that it is possible to obtain two-dimensional ferromagnetic order in insulating Cr2 Ge2 Te6 (ref.5 ) and CrI3 (ref.6 ) at low temperatures. Here we develop a device fabrication technique and isolate monolayers from the layered metallic magnet Fe3 GeTe2 to study magnetotransport. We find that the itinerant ferromagnetism persists in Fe3 GeTe2 down to the monolayer with an out-of-plane magnetocrystalline anisotropy. The ferromagnetic transition temperature, T c, is suppressed relative to the bulkT c of 205 kelvin in pristine Fe3 GeTe2 thin flakes. An ionic gate, however, raisesT c to room temperature, much higher than the bulkT c . The gate-tunable room-temperature ferromagnetism in two-dimensional Fe3 GeTe2 opens up opportunities for potential voltage-controlled magnetoelectronics7–11 based on atomically thin van der Waals crystals. Monolayers of Fe3 GeTe2 exhibit itinerant ferromagnetism with an out-of-plane magnetocrystalline anisotropy; ionic gating raises the ferromagnetic transition temperature of few-layer Fe3 GeTe2 to room temperature.